Where wonder grows - González, Xelena (Cinco Puntos Press, an imprint of Lee & Low Books Inc., 2022)
Three girls follow their grandmother into her garden, where they examine her collection of rocks, crystals, shells, and meteorites and learn about the marvels they reveal.